Tiam1 as a signaling mediator of Nerve Growth Factor-dependent neurite outgrowth - Shirazi Fard, Shahrzad (2010)
Nerve Growth Factor (NGF)-induced neuronal differentiation requires the activation of members of the Rho family of small GTPases. However, the molecular mechanisms through which NGF regulates cytoskeletal changes and neurite outgrowth are not totally understood. In this work, we identify the Rac1-specific guanine exchange factor (GEF) Tiam1 as a novel mediator of NGF/TrkA-dependent neurite elongation. In particular, we report that knockdown of Tiam1 causes a significant reduction in Rac1 activity and neurite outgrowth induced by NGF. Physical interaction between Tiam1 and active Ras (Ras- GTP), but not tyrosine phosphorylation of Tiam1, plays a central role in Rac1 activation by NGF. In addition, our findings indicate that Ras is required to associate Tiam1 with Rac1 and promote Rac1 activation upon NGF stimulation. Taken together, these findings define a novel molecular mechanism through which Tiam1 mediates TrkA signaling and neurite outgrowth induced by NGF.